The Effect Of Using Short Story On Student's English Reading Comprehension - Leli Julia Sari, Yusnita Nasution (Pusdikra Publishing, 2023)
This study aims to determine whether there is a significant effect of using short stories on improving reading comprehension for grade students VIII Mts Yp. Haji Datuk Abdullah. This research method is a qualitative method. The samples of this study were students of class VIII-1 and VIII-2 at Mts Yp. Haji Datuk Abdullah in the 2021/2022 school year. In this study, researcher took 60 students as samples. The researcher used 10 multiple choice questions to measure students' reading comprehension. In the data collection technique, the researcher used pre-test, treatment and post-test by giving a reading comprehension test. The results of this study indicate that there is a significant effect from the use of short stories. This can be seen from the difference in students' average scores from the pre-test and post-test scores in the experimental class which increased.The t-test average post-test score in the control class was 52 while the post-test score in the experimental class was 75 higher. then control class. in brief, the short story strategy can be applied to improve students' reading comprehension.